2016
DOI: 10.1007/s00381-016-3084-4
|View full text |Cite
|
Sign up to set email alerts
|

Infected cephalohematomas and underlying osteomyelitis: a case-based review

Abstract: When an infected cephalohematoma is suspected, aspiration of hematoma fluid should be performed for both diagnostic and therapeutic purposes. Infectious symptoms should warrant prompt investigation and treatment, which may include drainage, debridement, and antibiotics. This report demonstrates that the combination of an infected cephalohematoma and underlying osteomyelitis might not be as uncommon as previously believed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Scalp hematomas occur in up to 4% of vacuum or forceps deliveries, but only in rare cases scalp hematomas become infected, most commonly by E-coli, Staphylococcus and Streptococcus species [9, 10]. Infected scalp hematomas may occur more often after needle aspiration, fetal monitoring, and instrumental delivery, as in our patient.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Scalp hematomas occur in up to 4% of vacuum or forceps deliveries, but only in rare cases scalp hematomas become infected, most commonly by E-coli, Staphylococcus and Streptococcus species [9, 10]. Infected scalp hematomas may occur more often after needle aspiration, fetal monitoring, and instrumental delivery, as in our patient.…”
Section: Discussionmentioning
confidence: 89%
“…Infected scalp hematoma should be suspected with increasing scalp hematoma, erythema, fluctuation, and relapse of a systemic infection. Clear signs of abscess in the scalp should be treated with incision, aspiration, antibiotics covering the most common microbes present in scalp hematomas, and often followed by surgical debridement [9, 10]. On day 2 our patient developed a scalp hematoma with no early signs of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Stuadt et al found only 17 cases of osteomyelitis in 81 total cases of infected cephalohematomas. 6 It is hypothesized that cephalohematomas can become infected via different routes. Hematogenous spread is believed to be causative in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiology. Osteomyelitis in neonates is usually due to hematogenous spread of bacterial infections or less frequently to direct inoculation as a result of a trauma or puncture wounds or surgery, infected cephalohematoma [14][15][16]. In preterm infants, direct injection of bacteria can result from heel or venipuncture and artery or vein umbilical catheterization.…”
Section: Introductionmentioning
confidence: 99%